ショウワキチ ノ チジョウ キショウ カンソク ソウチ コウシン ゼンゴ ノ データ ノ キンシツセイ ニ ツイテ - 佐藤, 健; サトウ, タケル; 東島, 圭志郎; ヒガシジマ, ケイシロウ; 安ヶ平, 一也; ヤスガハラ, カズヤ; 村方, 栄真; ムラカタ, エイシン; Sato, Tatsuru; Higashijima, Keishiro; Yasugahira, Kazuya; Murakata, Eishin (2003)
P(論文) 昭和基地の地上気象観測装置は,第39・40次隊により1997年と1998年の2カ年計画で更新された. 新システムは,1999年2月1日より正式運用を開始したが,その後1年間は旧装置での観測も継続して行い,両装置の比較のためのデータを取得した. 比較観測の結果から,次のことが分かった.1) 両装置の観測データは,概ね精度の範囲内で一致し,新旧データの均質性が保たれていた.2) しかし,一部の要素については,観測値に僅かであるが無視できない差異が生じていた.3) これらの差異は,測器感部やデータ処理の方法,設置位置の変更など装置の仕様変更に起因していた. 本稿では,これら両装置の観測値の差異とその特徴,データの均質性などについて考察した結果を報告する. The surface meteorological observation system was replaced over two years, 1997 and 1998, at Syowa Station in Antarctica. The new system has been formally operated since February 1st 1999. Operation of the old system was continued for one year afterward in order to compare data from both systems. The results of comparison of both systems are as follows: 1) The observation data from both systems agree within the accuracy of the system. The homogeneity of old and new data has been preserved.2) However, some observed quantities show differences that cannot be disregarded although they are small.3) These differences originated from changes of sensor, data-processing method, and installation position. This paper reports the results considering differences in observational values obtained from the two systems, characteristics of data and homogeneity of data. departmental bulletin paper